If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(w + 5) = 2w + 35 Reorder the terms: 3(5 + w) = 2w + 35 (5 * 3 + w * 3) = 2w + 35 (15 + 3w) = 2w + 35 Reorder the terms: 15 + 3w = 35 + 2w Solving 15 + 3w = 35 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. 15 + 3w + -2w = 35 + 2w + -2w Combine like terms: 3w + -2w = 1w 15 + 1w = 35 + 2w + -2w Combine like terms: 2w + -2w = 0 15 + 1w = 35 + 0 15 + 1w = 35 Add '-15' to each side of the equation. 15 + -15 + 1w = 35 + -15 Combine like terms: 15 + -15 = 0 0 + 1w = 35 + -15 1w = 35 + -15 Combine like terms: 35 + -15 = 20 1w = 20 Divide each side by '1'. w = 20 Simplifying w = 20
| 24x+4=4(5x-7) | | 9y-(5y-3)=33 | | 4x+10=x+70 | | 6-x/7=-2 | | 2(u+7)=4u+26 | | 8x-4+9=2 | | 5a+3b-2a= | | h=t^2-9t+25 | | 2(m-4)=3m-10 | | 6m+4m-1=39 | | -18+12n=10+5n | | 6x/5=30 | | 4x+29x+30= | | 5+2x=-16 | | p=r+s-7whatisr | | 180-x=5x+3x | | -7=v-4 | | 6y-1=4y-5 | | 163.25=106.45 | | 15x+12=66-3x | | V=11h-16 | | 7v-1=4(v+2) | | 7d-8=6d+1 | | -9a-b-2a-10b= | | 26-8k=(8k-2) | | 5x^3+.5x^2-1.5x-210=0 | | (X^2-8x-8)(7x^2-3x-7)=0 | | 5k+9=2k | | 2v-4=-10 | | 2x-4=110 | | x/3−6=9 | | z=(12x+48)96y |